Governing green open space in indonesia: barriers and opportunities to enhancing enviromental quality - Yusuf, Muhamad; Kurniasih, Denok; Saputra, Anggara Setya (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
This article discusses the enhancing of  governing green open space in Indonesia. It began by looking at the current condition of green open space in Indonesia, highlighting the barriers faced in governing these areas, looking at opportunities to enhancing, and making recommendations to improve green open space governance. Literature review on governance frameworks that can maximize the potential of green open spaces in Indonesia. The results of this study show that there are several constraints in governing green open spaces, including less awareness and understanding among stakeholders, limited funding and resources, inadequate urban planning, limited community involvement, limited law enforcement and monitoring, urbanization and land scarcity, and weak coordination among government agencies in their management bodies. Our findings point to opportunities in governing greenspace areas, by learning from successful projects, exploring global good practices; innovative financing and partnerships; integrating greenspace into urban planning for cohesive neighborhoods; engaging communities for long-term success and shared responsibility; raising awareness of the value of greenspace through educational campaigns; and utilizing technology for data-driven decision-making and community participation. These opportunities contribute to policy recommendations that can be used by the central government and local governments to improve green open space governance in Indonesia.